2018
DOI: 10.1073/pnas.1815294115
|View full text |Cite
|
Sign up to set email alerts
|

Receptor selectivity from minimal backbone modification of a polypeptide agonist

Abstract: Human parathyroid hormone (PTH) and N-terminal fragments thereof activate two receptors, hPTHR1 and hPTHR2, which share ∼51% sequence similarity. A peptide comprising the first 34 residues of PTH is fully active at both receptors and is used to treat osteoporosis. We have used this system to explore the hypothesis that backbone modification of a promiscuous peptidic agonist can provide novel receptor-selective agonists. We tested this hypothesis by preparing a set of variants of PTH(1–34)-NH2 that contained a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…The demonstration that incorporation of a b-residue can abrogate TCR engagement without compromising MHC-II binding mirrors past findings with an MHC-II binding peptide derived from MOG (46). Past work has shown that b-residue incorporation can impart selectivity between receptor subtypes (68) and between distinct signaling pathways for a single receptor (69). The replacement of awith b-residues might therefore represent a general strategy for creating MHC-II binding peptides with unique functional profiles.…”
Section: Discussionsupporting
confidence: 64%
“…The demonstration that incorporation of a b-residue can abrogate TCR engagement without compromising MHC-II binding mirrors past findings with an MHC-II binding peptide derived from MOG (46). Past work has shown that b-residue incorporation can impart selectivity between receptor subtypes (68) and between distinct signaling pathways for a single receptor (69). The replacement of awith b-residues might therefore represent a general strategy for creating MHC-II binding peptides with unique functional profiles.…”
Section: Discussionsupporting
confidence: 64%
“…17 We therefore hypothesize that modifying the backbone of exenatide might improve its proteolytic stability and prolong its activity in vivo. However, backbone modications at the N-terminal part of incretins and other ligands of class B GPCRs have scarcely been reported 15,[18][19][20] which reects the difficulty to mimic the complex network of interactions in the binding pocket of the receptor transmembrane domain. 21 Herein we report the utilization of a ureido residue replacement at position 2 of GLP-1 analogues to improve their pharmacodynamic properties via selective enhancement of G protein-dependent cAMP signalling and altered GLP-1R trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is appealing because α→β replacements inhibit proteolytic degradation, which leads to very short in vivo lifetimes for natural peptide hormones. We have previously discovered that α→β modifications can modulate receptor selectivity or signaling profile relative to an all‐α prototype …”
Section: Figurementioning
confidence: 99%